Алексей Толстой - Варламов Алексей Николаевич (Жизнь замечательных людей, 2008)
Прим. : с. 561-581 Экземпляры: ф. 2 (20120627) / Инвентарный номер: 98802 / Цена: 440.59 / Сис.шифр: 83.3(2Рос=Рус)6 / Авт.знак: В 18 / ББК: 83.3(2Рос=Рус)6